Lignocellulosic Waste as a Sole Substrate for Production of Crude Cellulase from Bacillus subtilis PJK6 Under Solid State Fermentation Using Statistical Approach - Kaur Prabhjot; Bhardwaj Shubhang; K. Bhardwaj Nishi; Sharma Jitender (Journal of Carbohydrates, 2018)
The agricultural organic wastes pose major environmental issues and their inappropriate disposal is a major cause of pollution while these as cheap lignocellulosic resources can be utilized for many value added products such as enzymes. The purpose of the present study was to utilize wheat bran as a sole substrate for enhanced cellulase production under submerged fermentation (SMF) or solid state fermentation (SSF) and optimize the various process variables involved in the selected fermentation type. In order to achieve high titer of cellulase, a central composite design (CCD) was constructed and performed for optimization of SSF with five process variables at five coded levels. A 25 full factorial design was constructed leading to a set of 50 experiments that were performed in triplicates. The key variables namely incubation time, temperature, wheat bran and tap water ratio, pH and inoculum size were evaluated. The optimization of the process variables resulted in 1.14 IU/ml of cellulase activity from Bacillus subtilis PJK6 under SSF using wheat bran as a sole organic substrate with tap water. The optimum conditions included incubation time- 72 h, temperature- 45oC, pH- 6, inoculum size- 14% with 1:4 as wheat bran and tap water ratio. The production of cellulase using only moistened wheat bran was demonstrated and found to be significantly controlled by incubation time and temperature while pH showed the least effect. The economic production of valuable and useful enzyme using agricultural residue was achieved at moderate conditions from a GRAS microbe that can benefit the industry as well as the environment.
Keywords: Cellulase